Modal noise mitigation for high-precision spectroscopy using a photonic reformatter - Pike, Fraser; Benoît, A.; MacLachlan, D. G.; Harris, Robert J.; Gris-Sánchez, I.; Lee, D.; Birks, T. A.; Thomson, R. R. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Recently, we demonstrated how an astrophotonic light reformatting device, based on a multicore fibre photonic lantern and a 3D waveguide component, c